HUMAN RESOURCE PRACTICES AND ORGANIZATIONAL PERFORMANCE. INCENTIVES AS MODERATOR - Abang Azlan, Mohamad; Lo, May Chiun; Maw, King La (Spiru Haret University, 2009)
It has become clear that firm performance has important implications for employees and organizations as confirmed by past researchers. This study examines human resource practices and the impact of incentives on manufacturing companies in the Malaysia context. Three types of human resource practices namely, performance appraisal, training, and information technology have been chosen as the focus of this research with the presence of incentives as moderator on organizational performance. This is imperative in order to ensure the successful management of employees and also to improve productivity and achievements of an organization. The research uses a sample of eighty-five firms in Sarawak, Malaysia, voluntarily participated in this study. The results have indicated that the two components of human resource (HR) practices namely, training and information technology have direct impact on organizational performance. It was found that incentive is positively related to organizational performance but did not moderate the relationship between both HR practices and organizational performance. Implications of the findings, potential limitations of the study, and directions for future research are suggested.